D2D data sharing partner selection mechanism based on privacy degree and stability degree - Zhangjian HUANG; Guohua YE; Zhiqiang YAO (网络与信息安全学报)
Device to device (D2D) data sharing has become a promising solution to offload cellular network traffic,but the privacy vulnerability and service instability of data sharing partners affect the quality of shared services.To solve this problem,a D2D data sharing partner selection mechanism based on degree of privacy degree and stability degree (named PSUS) was proposed.Firstly,the privacy information of the provider was abstracted and summarized,and the privacy measurement method was built according to the privacy preferences of the provider and the historical records of shared services,and the privacy degree of the provider in different shared services was obtained.Then,the data sharing process was designed based on privacy degree,and the provider cached data under the constraints of privacy preferences and participates in sharing services with low privacy to meet the provider's privacy requirements.Finally,on the basis of the provider who has satisfied the privacy requirements,a multi-index evaluation method was designed to evaluate the service stability of providers to select stable sharing partners.The feasibility of the proposed mechanism was demonstrated by analysis of performance.